Coaching styles and sports motivation in athletes with and without intellectual impairments - Sakalidis, K. E.; Hettinga, F. J.; Ling, F. C. M. (PLOS ONE, 2023)
The cognitive limitations of athletes with Intellectual Impairments (II) may influence their sport behaviour and lead them to rely on coaches` support. However, it is still unclear how II may influence sports performance progression and motivation and how coaches perceive their athletes with II and coach them. Thus, this study aims to examine 1) coach`s perceptions of motivation and performance progression in athletes with and without II, 2) coaching style (dis)similarities, and 3) the association between these factors. Coaches of athletes with (n = 122) and without II (n = 144) were recruited and completed three online questionnaires, analysed using a series of non-parametric analyses (p = .05). Results showed that perceived performance progression and controlled motivation were higher of athletes with II while perceived autonomous motivation was higher of athletes without II. No coaching style differences were found between the two groups. Additionally, a need-supportive coaching style negatively predicted amotivation, and a need-thwarting coaching style predicted lower autonomous motivation in athletes with II only. Overall, it seems that the coaches perceived that their athletes with II demonstrate different motivations and react dissimilarly to their coaching styles compared to athletes without II. They may also adopt different standards of sporting success for them. Due to these differences, it is important to offer appropriate training and knowledge to coaches about disability sports and the adaptations needed to effectively coach athletes with II. In summary, this paper gives some insights about the coach-athlete relationship and highlights the necessity to further support the sports development of people with II.